The changing structure of production: Argentine agriculture 1988-2002 - Marcos Gallacher (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2009)
The agricultural sector of many countries shows increasing farm size with corresponding decrease in farm numbers. Despite abundant research, the determinants of changes in firm numbers and size have not been clearly identified. This paper attempts to explain small firm survival in Argentine agriculture in the 1988-2002 period. The evidence suggests that labor market considerations, as well changing optimal size in response to production specialization are important factors affecting small-firm disappearance. In contrast, factor proportions (the K/L ratio) does not appear to have an impact on changes in firm size.
Keywords: D2; Q12; 330; economies of scale; Argentine agriculture; agricultural labor markets; Landwirtschaft; Betriebsgrößenstruktur; Skalenertrag; Ländlicher Arbeitsmarkt; Argentinien